The Village Fund Management Accountability and SDG Achievement in Loa Duri Ilir, Kutai Kartanegara, East Kalimantan, During the Covid-19 Pandemic - Camelia Putrini; Agus Prasetyo; Hartanto Hartanto (Universitas Serang Raya, 2023)
This study examines the accountability of village fund management as the sole source of funding in an era of economic hardship brought on by the Covid-19 pandemic in support of the Village SDGs policy. Because the research target was in one of the Covid-19 pandemic's black zones in Indonesia, the study used a qualitative method with internet interviews. To achieve accountability, the Village government avoids abuse of authority by the village head as the highest authority in the management of the Village Fund, encourages community participation and transparency in the Village Fund management process, and implements programs in accordance with the village typology as an independent village. Finally, the village adopted reporting processes in compliance with applicable regulations and made proper use of SISKEUDES as policy accountability implementation. According to the research, village funds are a solid source of funds to support the Village SDGs agenda. Accountability for village fund management is a critical issue that must be considered to ensure the sustainability of village funds.